Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan dan Beban Pajak Kini Terhadap Manajemen Laba: Studi Empiris Perusahaan Manufaktur Sub Sektor Industri yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2019—2021 - Bernadetta Erika Tambunan; Tutty Nuryati; Uswatun Khasanah (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
This study reviews the effect of tax planning, deferred tax expense and current tax expense on earnings management. The purpose of writing this article is to build a hypothesis on the influence between variables for use in further research. The results of this literature review article are: Tax planning has an effect on earnings management, Deferred tax expense has an effect on earnings management, and Current tax burden has an effect on earnings management.